Sº and jarosite behavior during recovery of values from the direct leaching residue of sphalerite using cyanide and glycine - Picazo, Nallely Guadalupe; Carrillo Pedroza, Francisco Raúl; Martínez Luévanos, Antonia; Soria Aguilar, Ma de Jesús; Almaguer Guzmán, Isaías (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
This paper reports the effect of the components of a direct leaching residue (jarosite and elemental sulfur), on the recovery of valuable metals such as gold and silver. Leaching media such as cyanide and mixtures of cyanide with glycine were used to recover the gold and silver from the residue; however, a low recovery of these metals was obtained. The above due to the negative effect of its components which cause problems in the extraction process such as encapsulation of silver (due to jarosite) and the formation of thiocyanate and re-precipitation of silver (due to sulfur). Various treatments prior to leaching were tested, finding that when the residue is desulfurized with perchlorethylene and subjected to an oxidizing alkaline hydrothermal treatment, the gold extraction increased from 39.73 to 88% and the silver extraction of 64.76 to 94.29%. Additionally, it was determined that when cyanide is assisted by glycine, the latter decreases its consumption during gold and silver leaching tests.
Keywords: Gold, silver, treatments, jarosite, elemental sulfur.